An assessment of pre-service education programs for secondary science teachers - Campos, Dionisia Florendo 1920-
This empirical research was designed to assess the pre-service education programs for secondary science teachers in the hope that the outcomes of this study may lead to the development of new ideas and new perspectives in the education of the teacher, particularly the science teacher.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Science teachers -- Training of -- Philippines; Evaluation